El tratamiento informativo de la inmigración en los medios de comunicación españoles. Un análisis de contenido desde la Teoría del Framing - Igartua Perosanz, Juan José; Muñiz Muriel, Carlos; Otero Parra, José Antonio; De la Fuente Juan, Montse (Estudios sobre el Mensaje Periodístico, 2007)
Adopting the Framing Theory as a basis, news treatment of immigration in Spanish mass media was analyzed, due to the potential role such media might play in the formation of stereotypes and prejudicial attitudes. One week of TV prime-time news and daily newspapers were revised from January to June 2004. 485 units of analysis were obtained. Results show that most of the news refer to negative issues, especially the news frame that links delinquency and immigration. Besides, those news frames are the most highlightened. Futhermore, results also show that television offers news with a higher degree of sensationalism. Eventually, a reflection about the socio-cognitive consequences of this media practice is made because it transforms a social problem into a public one.